Ataluren/ivacaftor combination therapy: Two N‐of‐1 trials in cystic fibrosis patients with nonsense mutations. Issue 7 (13th April 2020) - Peabody Lever, Jacelyn E.; Mutyam, Venkateshwar; Hathorne, Heather Y.; Peng, Ning; Sharma, Jyoti; Edwards, Lloyd J.; Rowe, Steven M.
Abstract: Premature termination codons (PTCs) in cystic fibrosis transmembrane conductance regulator (CFTR) produce nonfunctional protein. No approved therapies exist for PTC mutations, including W1282X. We hypothesized that ivacaftor, combined with readthrough therapy, may benefit W1282X patients. Two N‐of‐1 clinical trials were conducted with ataluren and ivacaftor in various combinations. No meaningful clinical benefit was observed in either patient with ivacaftor alone or ataluren/ivacaftor combination. However, isolated improvements of uncertain significance were noted by a nasal potential difference (NPD) and FEV1 % with ivacaftor in Patient‐1 and with ataluren/ivacaftor combination by NPD and body mass index in Patient‐2. Drug regimen composed of readthrough agents and potentiators warrant further development for W1282X and other CFTR nonsense mutations.